2016
DOI: 10.1016/j.cogsc.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The influence of interunit carbon–carbon linkages during lignin upgrading

Abstract: a b s t r a c tThe cleavage of b-O-4 linkages in lignin can generate monomers with a phenyl propane structure that can easily be upgraded into valuable hydrocarbon biofuels and renewable aromatic chemicals. High-yield lignin monomer production from extracted (or technical) lignin that is produced in a practical way could facilitate the productivity and profitability of biomass conversion processes. However, interunit carbon ecarbon (CeC) linkages present in native lignin or formed during lignin condensation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 28 publications
2
58
0
Order By: Relevance
“…[1] The b-aryl ether unit (also known as the b-O-4 linkage) that features abenzylic secondary hydroxyl at Ca position and aprimary hydroxyl at Cg position is the most abundant interunit linkage,a nd ar elatively delicate portion of the lignin polymer. [2] Most delignification and lignin depolymerization processes in the pulp and paper industry and biorefineries are based on the cleavage of these b-O-4 bonds. [3] Recently,s everal groups have explored at wo-step lignin depolymerization strategy pioneered by Stahl and co-workers [4] based on the selective oxidation of the a-OH into aketone,which reduces the bond dissociation enthalpy of the associated b-aryl ether bond.…”
mentioning
confidence: 99%
“…[1] The b-aryl ether unit (also known as the b-O-4 linkage) that features abenzylic secondary hydroxyl at Ca position and aprimary hydroxyl at Cg position is the most abundant interunit linkage,a nd ar elatively delicate portion of the lignin polymer. [2] Most delignification and lignin depolymerization processes in the pulp and paper industry and biorefineries are based on the cleavage of these b-O-4 bonds. [3] Recently,s everal groups have explored at wo-step lignin depolymerization strategy pioneered by Stahl and co-workers [4] based on the selective oxidation of the a-OH into aketone,which reduces the bond dissociation enthalpy of the associated b-aryl ether bond.…”
mentioning
confidence: 99%
“…Lignin depolymerization and condensation are dominant modifications for carbohydrate‐orientated biomass fractionation, such as Kraft, soda, sulfite, and organosolv pulping, and acid‐based pretreatment for cellulosic ethanol production. These reactions lead to formation of intra‐ or inter‐unit C−C linkages, especially in acidic conditions . Our previous study revealed condensed lignin structures from batch fractionation of bamboo if aqueous formic acid was used at 101 °C .…”
Section: Resultsmentioning
confidence: 99%
“…These reactions lead to formation of intra-or inter-unit CÀCl inkages, especially in acidic conditions. [30] Our previous study revealed condensed lignin structures from batch fractionation of bamboo if aqueous formic acid was used at 101 8C. [31] Because thesec hemical linkages require more energy to be cleaved, condensed lignin tends to be less susceptible to depolymerization by chemical catalysis.…”
Section: Quantitative Analysis Of Lignin Structuresmentioning
confidence: 99%
“…It is predominately formed through radical coupling between coniferyl, sinapyl, and p ‐hydroxyphenyl alcohol, which results in different interunit linkages formed by C−C and C−O bonds . The β‐aryl ether unit (also known as the β‐O‐4 linkage) that features a benzylic secondary hydroxyl at Cα position and a primary hydroxyl at Cγ position is the most abundant interunit linkage, and a relatively delicate portion of the lignin polymer . Most delignification and lignin depolymerization processes in the pulp and paper industry and biorefineries are based on the cleavage of these β‐O‐4 bonds …”
Section: Figurementioning
confidence: 99%